The Relevance Of The Concept Of Faith To Michael J Losier's Law Of Attraction Theory To Happiness On Life In Perspective Of Transpersonal Psychology (Journal Intellectual Sufism Research (JISR), 2023)
This study explains the Relevance of Konep Iman to Michael J Lostier's Law Of Attraction Theory with Life Happiness in the Perspective of Transpersonal Psychology.  The study of this research is based on the law of Law of Attraction whose existence in modern times is greatly increased. The concept will be analyzed based on relevance to faith.  This is because modern society today already believes in the existence of these laws and has been practiced in everyday life. This research uses qualitative research methods and obtains data using literature based on written data in the form of journals, books, articles in accordance with the object of the theme studied. The analysis in this study is descriptive qualitative, this paper analyzes the concept of Law of Attraction (LoA) theory with the relevance of faith and happiness according to the study of transpersonal psychology. In this discussion it was found that the theory of the Law of Attraction (LoA) can add confidence and constancy of prayer to God, with an explanation of the mechanisms, thought waves, and processes of the universe in attracting what is believed and thought so that happiness is formed in life.
Keywords: The Concept of Faith, the Law of Attraction, and happiness Transpersonal Psychology